Unlocking student well-being: the serial mediation of screen time and emotion management ability in the physical activity-life satisfaction link, moderated by health literacy - Liu, Qi; Zhu, Wei-dong; Han, Shanshan; Lou, Hu; Li, Bo; Liu, Tao (Frontiers in Public Health, 2025)
ObjectiveThe present study aims to explore the influence of physical activity on Satisfaction with Life in a sample of university students. It examines the serial mediating roles of screen time and emotional management ability in the relationship between physical activity and Satisfaction with Life. Furthermore, it explores the moderating effect of health literacy on the path from emotional management ability to Satisfaction with Life.MethodsThe study employed a stratified, cluster, and multi-stage sampling strategy to collect demographic information. Relevant data about university students’ physical activity, Satisfaction with Life, screen time, emotional management ability, and health literacy were obtained through the Wenjuanxing online survey platform. A total of 24,979 valid questionnaires were collected and included in the analysis.ResultsThe present research investigated the relationship between physical activity and Satisfaction with Life in university students, focusing on the mediating and moderating mechanisms. The findings indicate that higher levels of physical activity are associated with greater life satisfaction. This relationship is explained in part by two sequential mediators: reduced screen time and improved emotional management ability. Physical activity appears to contribute to lower screen time, which in turn supports better emotional management, ultimately leading to higher life satisfaction. Additionally, health literacy was found to strengthen the connection between emotional management and life satisfaction—students with stronger health literacy skills derived greater satisfaction benefits from their ability to manage emotions.ConclusionThis research elucidates the influence of physical activity, screen time, and emotional management ability on the Satisfaction with Life of university students. The results suggest that interventions targeting increased physical activity, reduced screen time, and enhanced emotion regulation may effectively promote Satisfaction with Life among this demographic. It is recommended that future interventions integrate evidence-based strategies for fostering healthy screen time practices, emotion regulation training, and comprehensive health education to optimize the physical and mental health of university students.